The effect of age on growth and development of the gonads pre- to post sexual maturity of Japanese quail (Coturnix japonica) - Khalid Chillab Kridie AL-Salhie (Kufa Journal for Agricultural Sciences)
A total number of 300 unsexed Japanese quail chicks one day old were randomly distributed in the metal cages to determine the optimal age of sexual activity for quail in Iraq by studying the growth and development of the gonads pre-to post sexual maturity. Data were collected during 4, 6, 8 and 10 weeks. Steroids hormone and gonads and oviduct development were studied. Highest testosterone and estrogen hormone levels were recorded on 8 and 10 weeks of age. Left and right testis weight, height, width and volume were recorded highest values on 8 and 10 weeks compared with 4 and 6 weeks . Histological parameter of testes sections indicated a complete development for a seminiferous tubules beginning 8 to 10 weeks . Ovary weight with follicles and oviduct weight were given highest values at 10 weeks old. It has been concluded that the optimal age of sexual activity for quail in Iraq could be situated around 8 weeks.